Origins of twinned microstructures in B12As2 epilayers grown on (0001) 6H-SiC and their influence on physical properties - Zhang, Yu; Chen, Hui; Zhang, Ning; Dudley, Michael; Gong, Yinyan; Kuball, Martin; Xu, Zhou; Zhang, Yi; Edgar, James H.; Zhang, Lihua; Zhu, Yimei (My University, 2009)
The defect structure in B[subscript]12As[subscript]2 epitaxial layers grown at two different temperatures on (0001) 6H-SiC by chemical vapor deposition (CVD) was studied using synchrotron white beam x-ray topography (SWBXT) and high resolution transmission electron microscopy (HRTEM). The observed differences in microstructures were correlated with the differences in nucleation at the two growth temperatures. The effect of the difference in microstructure on macroscopic properties of the B[subscript]12As[subscript]2 was illustrated using the example of thermal conductivity which was measured using the 3-ω technique. The relationship between the measured thermal conductivity and observed microstructures is discussed.